2020
DOI: 10.1177/1059840520946378
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Media Addiction in Korean Elementary School Children

Abstract: The aim of this study was to identify the prevalence of media addiction and its associated factors in elementary school children based on the problem behavior theory. This cross-sectional study was a secondary data analysis using national data from the 10th Panel Study on Korean Children 2017, which included 1,078 families of third-grade students (8–9 years of age). Descriptive statistics were used to examine the prevalence of media addiction, and logistic regression analysis was conducted to identify factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 63 publications
(109 reference statements)
1
13
0
Order By: Relevance
“…A study of elementary school students in Korea found that PIU is related to gender, a mother’s educational level, spending time without parents, media exposure time, personal feelings such as happiness, and parenting style [ 6 ]. Influencing factors related to PIU of children and adolescents are classified into family, school, and individual dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…A study of elementary school students in Korea found that PIU is related to gender, a mother’s educational level, spending time without parents, media exposure time, personal feelings such as happiness, and parenting style [ 6 ]. Influencing factors related to PIU of children and adolescents are classified into family, school, and individual dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Across studies carried out in Eastern countries, the percentage of children classified as potential 'mobile phone users with problems' or 'risky media users' ranged between 20.9% [60] and 22.91% [61]. Moreover, adolescents showed higher PMU as compared to children.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies significantly associated the amount of children's time spent consuming media with PMU [68,69]. Children involved in the 'high-risk group' of PMU [61,[69][70][71] were found more prone to consume media more than 2 h a day, while those in the 'no-risk group' less than 2 h a day [61,69].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations